Influence of speech stimuli in the auditory perceptual identification of hypernasality in individuals with cleft lip and palate - de Castro Marino, Viviane Cristina [UNESP] (2020)
Purpose: To investigate the influence of speech stimuli in the auditory perceptual identification of hypernasality in individuals with Cleft Lip and Palate (CLP). Methods: Speech samples from 80 individuals with operated unilateral CLP, ages ranged from nine to 17 years (the mean age of: 12y7m), both genders, were edited for this study. Samples were recorded over the production of nine different speech stimuli, including counting and short sentences characterized by oral sounds, one loaded with low pressure consonants and seven loaded with high pressure consonants. Three speech-language pathologists rated the presence or absence of hypernasality while analyzing 864 recordings (80 individuals X 9 stimuli + 144 repeated recordings, for measuring the intra-rater agreement). Intra-rater and inter-rater indexes of agreement were established for all nine stimulus conditions. The indexes of inter-rater agreement were compared using the Z test (p<0.005), with samples comprising significant indexes of agreement interpreted as better stimuli for identifying the hypernasality in these individuals. Results: Intra-rater agreement for high pressure stimuli with voiced consonants were significantly lower than indexes for other stimuli. Inter-rater agreement between each pair of SLPs ranged from 0.11 (plosive voicing stimuli) to 0.57 (12 short sentences, one of each high pressure consonant). The values of mean inter-rater agreement between all SLPs was 0.47 indicating moderate agreement for identifying hypernasal speech. Conclusion: Speech recordings obtained over the production of longer speech samples including 12 short sentences, for instance one for each high pressure consonant, may favor inter-rater agreement for identifying hypernasality.